2015
DOI: 10.3177/jnsv.61.s76
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Signal Transduction and Gene Expression by Vitamin E via PI3Kγ/PKB and hTAP1/SEC14L2-Mediated Lipid Exchange

Abstract: SummaryThe ability of vitamin E to modulate signal transduction and gene expression has been observed in numerous cell culture and animal studies. These cellular signalling effects of vitamin E have been mainly explained as result of protection of lipids and signal transduction enzymes from random modification by free radicals or by specifically influencing their redox state. Alternatively, the observed signalling may reflect specific interactions of vitamin E with enzymes, structural proteins, and transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Nonantioxidant function of α‐Toc has recently attracted interest, and the number of reports dealing with this aspect has been increasing . α‐Toc (10–50 µM) induced the transcription and activation of peroxisome proliferator‐activated receptor γ (PPAR‐γ) via the increase in intracellular concentrations of a PPAR‐γ endogenous ligand 15‐deoxy‐Δ12,14‐prostaglandin J2 in adipocytes, leading to the upregulation of adiponectin expression, independent of an antioxidant effect .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonantioxidant function of α‐Toc has recently attracted interest, and the number of reports dealing with this aspect has been increasing . α‐Toc (10–50 µM) induced the transcription and activation of peroxisome proliferator‐activated receptor γ (PPAR‐γ) via the increase in intracellular concentrations of a PPAR‐γ endogenous ligand 15‐deoxy‐Δ12,14‐prostaglandin J2 in adipocytes, leading to the upregulation of adiponectin expression, independent of an antioxidant effect .…”
Section: Discussionmentioning
confidence: 99%
“…Two vitamin E isoforms (α‐ and γ‐Tocs) directly bound PKCα, and thereby the former inhibited nonoxidative cofactor‐dependent PKCα activity and the latter enhanced it in vitro . Furthermore, α‐Toc has been reported to modulate the activity of PI3K involved in cell signal transduction . As α‐Toc can modulate the catalytic activity of several enzymes directly involved in cell signal transduction , we examined the effects of α‐Toc on the cell polarization and directional cell migration essential for wound healing and the related cell signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a peroxyl radical-scavenging antioxidant, vitamin E is suggested to prevent the generation of free radicals and inhibit lipid peroxidation (182). Further, the ability of vitamin E to modulate signal transduction and gene expression has led researchers to focus on vitamin E analogs in search of new targets for treatments in melanoma development (190). A clinical trial conducted by Placzek et al found a photoprotective effect after 3 months of supplementation with a-tocopherol, and the participants seemed to have increased resistance to UVB-induced sunburn and protection from DNA damage (191).…”
Section: Vitamin Ementioning
confidence: 99%
“…As a peroxyl radical‐scavenging antioxidant, vitamin E is suggested to prevent the generation of free radicals and inhibit lipid peroxidation . Further, the ability of vitamin E to modulate signal transduction and gene expression has led researchers to focus on vitamin E analogs in search of new targets for treatments in melanoma development . A clinical trial conducted by Placzek et al .…”
Section: Vitaminsmentioning
confidence: 99%